SPONTANEOUS RHINORRHOEA SECONDARY TO NORMAL-PRESSURE PARTIAL EMPTY SELLA SYNDROME - Yap, Xiao Ling; Chua, Yi Jiang; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Empty sella syndrome is a disorder where the sella turcica is partially or completely filled with cerebrospinal fluid (CSF), resulting in compression and displacement of the pituitary gland. Empty sella is frequently coupled with increased intracranial pressure which causes spontaneous CSF leaks. Some people may experience normal-pressure CSF leaks, which can be due to idiopathic or congenital abnormalities. Both high-pressure and normal-pressure CSF leaks are commonly seen in middle-aged obese women. CASE A 43-year-old obese female with a BMI of 34.9 kg/m² presented with a two-day history of headache and clear nasal discharge persisting for a month. She reported no weakness or visual disturbances. Upon examination, her blood pressure measured 142/70 mmHg, her Glasgow Coma Scale was intact, and her neurological assessment revealed no abnormalities. The ophthalmological evaluation showed no signs of papilledema. Subsequently, a lumbar puncture was performed, indicating a normal opening pressure of 12 cm H₂O. Brain MRI revealed a partially empty sella, while CT imaging of the paranasal sinuses aimed to identify the cause of the CSF leak, was suggestive of cribriform plate dehiscence. Evaluation of anterior pituitary hormones yielded results within normal ranges. The case was then referred to a neurosurgical team for further evaluation and potential surgical intervention. The occurrence of a spontaneous cCSF leak frequently coincides with the radiographic discovery of an empty sella. Its clinical manifestation can vary, encompassing symptoms such as headaches, rhinorrhoea, visual impairments, and hormonal imbalances. Assessing pituitary hormone levels is crucial, with hormonal supplementation warranted when deficiencies are identified. Surgical intervention is essential in managing CSF leaks to mitigate potential complications like meningitis and brain abscesses. CONCLUSION A CSF leak is important to be recognised at the initial presentation, as surgical intervention is required to reduce the complication of infections.